(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In this article, the requirements of the educational system of our republic, current tasks, the high results achieved under the reforms and the pedagogical features of the formation of the spiritual and moral education of young people, and the role of the family and the educational system are expressed in this article.